Grid Services for Multi-objective Optimisation - Goteng, Gokop; Tiwari, Ashutosh; Roy, Rajkumar (Cranfield University Press, 2009)
The emerging grid technology is defined as an infrastructure for secure and coordinated large-scale resource sharing. In this paper, we describe the architecture and grid services of DECGrid. DECGrid enables distributed design experts to collaborate and share resources during design optimisation. Mathematical models are built using services by experts. These models are then directly linked to NSGA-II optimisation algorithm service and allow design experts to enter design parameters of their choice. A real-life case study-welded beam problem was used to validate the prototype. The results obtained showed a wider spread in the solution space compared to the results in literature.
Organised by: Cranfield University
Keywords: Grid services; Multi-objective optimisation; design optimisation; Mathematical model